ANALISA ATAS PELAKSANAAN AUDIT MUTU INTERNAL UNTUK MENGEVALUASI EFEKTIFITAS PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2000 (Studi Kasus pada PT. Murni Cahaya Pratama) - Syarief Gerald Prasetya (STIE Binaniaga, 2010)
Quality of Internal Audit is an activity which is very important and is a requirement in the implementation of ISO 9001:2000 standard, which aims to monitor the quality of the verifying the suitability and effectiveness of the implementation of the system of quality compared to the reference standards and policies that have been determined. Quality of Internal Audit is an assessment process and system to see whether the processes and systems in line with documented procedures and to see the effectiveness of the procedure. By doing this assessment, the company will know the condition or situation at this time. In the end, the results of this audit will be used as a tool / material improvement in the action / prevention of at improvement. Therefore, international standards emphasize the importance of audits as a means of monitoring and verification. ISO 9001:2000 is an international standard for quality management system. ISO 9001:2000 define the requirements and recommendations for the design and evaluation of a quality management system, which has the goal to ensure that an organization will provide products that comply with the requirements specified. The ISO 9001:2000 is only quality management standard and is not a standard product. But expected that the product resulting from international quality management system will has a suitable quality this. Implementation of Internal Audit Quality in the PT. Murni Cahaya Pratama program showed that the Internal Audit Quality is in accordance with plans and procedures. Results of Internal Audit Quality use as the improvement efforts for both systems, processes and products. The quality management system ISO 9001:2000 which is applied in PT. Murni Cahaya Pratama quite effective and efficient. However, there are several things that indicate the occurrence of inefisiensi and inefektivitas, this can be viewed from the inconsistency or the findings found at time internal audit been held of it occurs because human error and the lack of knowledge and understanding of the importance of documentation, especially new employees . Advice from the author on the results of the Internal Quality Audit was done in PT. Murni Cahaya Pratama is, for 2009 ISO 9001:2000 and Internal Quality Auditor training should been held immediately, so that all employees understand the importance of procedures and can implemented in their daily activities. Also to improve auditor's ability. Set procedures for the return of goods from the customer (return), so that when the Technical Service bring the returned goods it can be treated accordance with the procedures applicable. Consistent in their assessment of suppliers and maintain records of these assessments. Keywords: Internal Audit Quality, Quality Management System ISO 9001:2000